4-picoline adsorption from aqueous solution by using baggage fly ash (BFA): Parametric, kinetic and thermodynamic aspects. Issue 11 (20th October 2022) - Pangarkar, Bhausaheb L.; Shrimal, Preena; Daware, Gaurav B.; Dabhade, Ganesh B.
Abstract: Numerous harmful characteristics of wastewater containing pyridine chemical have a significant negative impact on human health. Therefore, it is preferred to remove it from effluent. The derivatives of pyridine are 2- and 4-picoline. In this work, an adsorption technique was used to remove 4-picoline from the effluent. Wastewater was treated to remove 4-picoline using the natural adsorbent baggage fly ash (BFA). 4-picoline adsorption rate of 82% was reported at pH 6.22, BFA adsorbent dosage of 4 g/L, and contact time of 6 h. The current investigation found that 85.83% of 4-picoline could be removed at its maximum with BFA at a temperature of 333 K. Investigations were also carried out into how the starting concentration and temperature affected the elimination of 4-picoline. According to the kinetic analysis, the process uses pseudo-second-order rate kinetics. The thermodynamics study also demonstrated that all temperatures could be predicted using the Freundlich and Langmuir equilibrium adsorption isotherm models. It further demonstrated that 4-picoline adsorption on BFA is an endothermic process. HIGHLIGHTS: This study confirmed that 4-picoline can effectively be removed from wastewater by using baggage fly ash as an adsorbent. The adsorption kinetics of 4-picoline on baggage fly ash follow the pseudo-second order rate expression. The Freundlich and Langmuir adsorption isotherm models are best suited for elimination of 4-picoline from wastewater using BFA. The maximum removal of 4-picoline was found up to 85.83%.